Structural elucidation of the lipopolysaccharide core region of the O-chain-deficient mutant strain A28 from Pseudomonas aeruginosa serotype 06 (International Antigenic Typing Scheme). - Masoud, H (1995)
The lipopolysaccharide (LPS) of the Pseudomonas aeruginosa serotype 06 rough-type mutant A28 was isolated by a modified phenol-chloroform-petroleum ether extraction method. Deoxycholate-polyacrylamide gel electrophoresis indicated a single band with mobility similar to that of the complete core region of the wild-type parent serotype 06 (International Antigenic Typing Scheme) strain. Compositional analysis of the LPS indicated that the core oligosaccharide was composed of D-glucose (three units), L-rhamnose (one unit), 2-amino-2-deoxy-D-galactose (one unit), L-glycero-D-manno-heptose (two units), 3-deoxy-D-manno-octulosonic acid (two units), L-alanine (one unit), and phosphate (two units). Under the mild conditions of hydrolysis with methanolic hydrogen chloride, a 7-O-carbamoyl substituent was observed on the second heptose residue. The glycan structure of the LPS was determined by employing one- and two-dimensional nuclear magnetic resonance spectroscopy and mass spectrometry-based methods with a backbone oligosaccharide that was obtained from the LPS by deacylation, dephosphorylation, and reduction of the terminal glucosamine. On the basis of the results of the present study and our earlier work with the P. aeruginosa 06-derived core-defective mutant R5 (H. Masoud, E. Altman, J. C. Richards, and J. S. Lam, Biochemistry, 33:10568-10578, 1994), a structural model for the complete core oligosaccharide is proposed.